2017
DOI: 10.1016/j.vetmic.2017.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, antigenic, and pathogenic characteristics of avian infectious bronchitis viruses genotypically related to 793/B in China

Abstract: assessed by an S1 gene comparison and a complete genomic sequence analysis, were isolated and identified from 2009 to 2014 in China. Phylogenetic analysis, network tree, similarity plot analysis, Recombination Detection Program 4(RDP4) and sequence comparison revealed that 12 of the 20 isolates were likely the reisolated vaccine virus. One isolate, ck/CH/LSD/110857, was shown to have originated from recombination events between H120-and 4/91-like vaccine strains that did not result in changes of antigenicity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…This is likely the case for the emergence of isolate γCoV/ck/China/I0114/14 in this study and also cases found in other countries such as in Italy and Spain (Moreno et al, 2017). In China, only limited numbers of 793/B type viruses have been detected and isolated in chicken flocks (Chen et al, 2015;Han et al, 2017). Furthermore, both the S1 gene and the complete genomic sequence analysis showed that most of the detected 793/B field strains were of the vaccines, or vaccine-derived strains .…”
Section: Discussionsupporting
confidence: 49%
“…This is likely the case for the emergence of isolate γCoV/ck/China/I0114/14 in this study and also cases found in other countries such as in Italy and Spain (Moreno et al, 2017). In China, only limited numbers of 793/B type viruses have been detected and isolated in chicken flocks (Chen et al, 2015;Han et al, 2017). Furthermore, both the S1 gene and the complete genomic sequence analysis showed that most of the detected 793/B field strains were of the vaccines, or vaccine-derived strains .…”
Section: Discussionsupporting
confidence: 49%
“…It has been reported that the side effects of the 4/91 vaccine might provide the basis for recombination with other strains. This phenomenon has been shown by several studies which have traced the emergence of many novel IBV strains to recombination events between the 4/91 vaccine and field strains (Feng et al, 2018;Han et al, 2017;Jiang et al, 2017Jiang et al, , 2018Liu et al, 2013;Mo et al, 2013;Ovchinnikova et al, 2011;Zhang et al, 2015Zhang et al, , 2016Zhou et al, 2017) in cases where the 4/91 vaccine strain could not provide effective protection against the field strains , leading to coinfection of the vaccine and field strains in the same chickens and ultimately resulting in recombination. In this study, we performed complete genome sequence analysis of strains I0718/17, I0722/17, I0724/17, and I0737/17 and confirmed the occurrence of recombination events at the 5′ ends of the S1 gene between a 4/91-like virus (GI-13 lineage) and a YX10-like virus (GI-19) (Xu et al, 2018), which contributed to the emergence of the IBV strains.…”
Section: Discussionmentioning
confidence: 87%
“…More recently, phylogenetic studies have reported that-in addition to the well-established lineages/genotypes such as GI-1, GI-7, GI-13, GI-19, GI-22, and GVI-1-a number of novel IBV variants have been isolated in China (Chen et al, 2015Han et al, 2017;Xu et al, 2016Xu et al, , 2018Zhao et al, 2017). These variants have been proved to be distinct from other reference strains on the basis of genetic characteristics and phylogenetic differences in the S1 gene (Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…High frequencies of recombination between vaccines (such as the 4/91 strain) and field strains have been reported frequently in China and other parts of the world (Cavanagh et al, 1992a,b;Jackwood et al, 2012;Liu et al, 2013;Han et al, 2017;Jiang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the emergent IBV strains in China may have different origins. It is considered that some of the IBV types circulating in China, such as Mass and 793/B, are the most widely distributed types worldwide and they may have infected Chinese chickens from an exogenous source, probably due to the use of live vaccines (Chen et al, 2015;Han et al, 2017). By contrast, some IBV types, such as LX4 and ck/CH/LDL/97I (Q1-like), are believed to have originated in China and spread to other regions of the world (Valastro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%